2017
DOI: 10.1186/s40635-017-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hyperoxia on microvascular endothelial cell proliferation and production of vaso-active substances

Abstract: BackgroundHyperoxia, an arterial oxygen pressure of more than 100 mmHg or 13% O2, frequently occurs in hospitalized patients due to administration of supplemental oxygen. Increasing evidence suggests that hyperoxia induces vasoconstriction in the systemic (micro)circulation, potentially affecting organ perfusion. This study addresses effects of hyperoxia on viability, proliferative capacity, and on pathways affecting vascular tone in cultured human microvascular endothelial cells (hMVEC).MethodshMVEC of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…On one hand, immature rat pups exposed to F I O 2 = 0.8 for 6 h display higher nitrotyrosine staining in the apical dendrites of neurons [ 137 ] (but the PO 2 -dependent proteins nitration appears to be controlled consistently by NO concentration [ 142 ]). On the other hand, human microvascular endothelial cells cultured at F I O 2 = 0.95 for 72 h do not show appreciable changes in neither the nitrotyrosine levels nor the eNOS mRNA and protein expression levels, regardless of PO 2 [ 143 ]. Observations gathered in rats exposed to 2.8 atm show that the augmented NO synthesis is associated with increased nNOS activation, Hsp90 and intracellular calcium entry [ 144 ].…”
Section: Nitric Oxidementioning
confidence: 99%
“…On one hand, immature rat pups exposed to F I O 2 = 0.8 for 6 h display higher nitrotyrosine staining in the apical dendrites of neurons [ 137 ] (but the PO 2 -dependent proteins nitration appears to be controlled consistently by NO concentration [ 142 ]). On the other hand, human microvascular endothelial cells cultured at F I O 2 = 0.95 for 72 h do not show appreciable changes in neither the nitrotyrosine levels nor the eNOS mRNA and protein expression levels, regardless of PO 2 [ 143 ]. Observations gathered in rats exposed to 2.8 atm show that the augmented NO synthesis is associated with increased nNOS activation, Hsp90 and intracellular calcium entry [ 144 ].…”
Section: Nitric Oxidementioning
confidence: 99%
“…Notably, both the ICA and VA shear rate were reduced in the present study following a single SCUBA dive; as such, repeated/prolonged exposure to hyperoxia may contribute to pressure-induced reductions in microvascular endothelial integrity following chronic participation in SCUBA diving (Attaye et al, 2017;Brueckl et al, 2006). Whether prolonged exposure to hyperoxia and hyperbaria during longer, deeper, colder and/or repetitive SCUBA dives would provoke changes to the functional responses of the cerebrovasculature requires further investigation.…”
Section: Stability In Functional Cbf Regulation Following a Scuba Divementioning
confidence: 63%
“…The reasons for the alterations in extra-cranial blood flow patterns are not clear but may relate to hyperoxia-induced endotheliummediated regulation of CBF as evidenced by reductions in ICA and VA shear rate following the SCUBA dive (Attaye et al, 2017;Brueckl et al, 2006). Further, the attenuation in ICA and VA shear rates is likely influenced by the observed 19% decrease in cardiac output; these data are consistent with the 17% reduction in cardiac output 30 min following a single SCUBA dive reported by Dujic and colleagues (2005).…”
Section: Cerebrovascular Regulation At Rest Following a Scuba Divementioning
confidence: 99%
“…Thus, because of the potential heterogeneity of the endothelial cells of the different tissues, the use of the primary endothelial cells, which were isolated from the metastatic site of interest, were to be preferred. Indeed, the studies showed significantly differed protein expression profiles in the HUVEC and endothelial cells of other origin, as well as the different behaviors of the foreskin endothelial cells versus the capillary endothelial cells from other organs [ 52 ]. While the HUVEC endothelial cells were frequently used in the model systems, the metastasis through the umbilical cord was a rare event with reliable data still lacking.…”
Section: Discussionmentioning
confidence: 99%